Amino acids and diabetes: implications for endocrine, metabolic and immune function - Newsholme, Philip; Abdulkader, F.; Rebelato, E.; Romanatto, T.; Pinheiro, C.; Vitzel, K.; Silva, E.; Bazotte, R.; Procopio, J.; Curi, R.; Gorjao, R.; Pithon-Curi, T. (Frontiers in Bioscience, 2011)
Aberrant alterations in glucose and lipid concentrations and their pathways of metabolism are a hallmark of diabetes. However, much less is known about alterations in concentrations of amino acids and their pathways of metabolism in diabetes. In this review we have attempted to highlight, integrate and discuss common alterations in amino acid metabolism in a wide variety of cells and tissues and relate these changes to alterations in endocrine, physiologic and immune function in diabetes.